Chicken Incubation Conditions: Role in Embryo Development, Physiology and Adaptation to the Post-Hatch Environment - Tona, K.; Voemesse, K.; N’nanlé, O.; Oke, O. E.; Kouame, Y. A. E.; Bilalissi, A.; Meteyake, H.; Oso, O. M. (Frontiers in Physiology, 2022)
Chicken hatching egg is a self-contained life-supporting system for the developing embryo. However, the post-hatch performance of birds depends on several factors, including the breeder management and age, egg storage conditions and duration before incubation, and the incubation conditions. Studies have determined the effect of incubation factors on chick post-hatch growth potential. Therefore, chick physical quality at hatch is receiving more and more attention. Indeed, although incubation temperature, humidity, turning and ventilation are widely investigated, the effects of several variables such as exposure of the embryo to high or low levels, time of exposure, the amplitude of variations and stage exposures on embryo development and post-hatch performance remain poorly understood. This review paper focuses on chick quality and post-hatch performance as affected by incubation conditions. Also, chick physical quality parameters are discussed in the context of the parameters for determining chick quality and the factors that may affect it. These include incubation factors such as relative humidity, temperature, turning requirements, ventilation, In ovo feeding and delay in feed access. All these factors affect chick embryo physiology and development trajectory and consequently the quality of the hatched chicks and post-hatch performance. The potential application of adapted incubation conditions for improvement of post-hatch performance up to slaughter age is also discussed. It is concluded that incubation conditions affect embryo parameters and consequently post-hatch growth differentially according to exposure time and stage of exposure. Therefore, classical physical conditions are required to improve hatchability, chick quality and post-hatch growth